PENGARUH STRATEGI ORIENTASI ORGANISASI TERHADAP MANAJEMEN RANTAI PASOK HIJAU DAN KINERJA BISNIS - Henilia Yulita (Jurnal Co Management, 2019)
Environmental pollution is a major problem that has the potential to cause the extinction of mankind on earth if it is not immediately addressed. Companies that have adopted green supply chain management believe that environmental awareness is a "win-win" for business and the environment. In Indonesia, poor transportation facilities and infrastructure have an impact on increasing transportation costs so that the average logistics costs for sales have also increased. However, this condition does not mean that the company cannot reduce its logistics costs, because by applying the Green Supply Chain Management concept, the company will have the opportunity to increase the efficiency of logistics activities thereby reducing the company's total logistics costs. The purpose of this study was to determine the Effect of Organizational Orientation Strategies on Green Supply Chain Management and Business Performance. This research is a type of quantitative research and is a causal research, with a total sample of 61 respondents who are MSME owners in the food sector. The statistical method used is Partial Least Square with hypothesis testing techniques using Structural Equation Modeling techniques with the help of SmartPLS 3.0 applications. The results of the study show that Organizational Orientation namely Supply Chain Orientation has no influence on Green Supply Chain Management; Environmental Orientation has an influence on Green Supply Chain Management; Green Supply Chain Management has a positive influence on Business Performance (Cost Efficiency, Consumer Effectiveness and Environmental Differences).